2023
DOI: 10.2478/cipms-2023-0011
|View full text |Cite
|
Sign up to set email alerts
|

Mephedrone – a synthetic derivative of cathinone

Abstract: Novel psychoactive substances (NPS) are a very diverse group of recreational drugs that mimic effects of classic drugs of abuse and, at least at the beginning, are not usually prohibited. Representative of this group is mephedrone – a cathinone derivative. It is widely used as a recreational drug, particularly among club guests. Mephedrone`s effects are compared to effects of cocaine and MDMA but are more short-lived and include: psychostimulation, enhanced empathy, reduced feeling of tiredness, euphoria, hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…84 However, not all the effects are only related to cathinone use, as polysubstance abuse (for example with alcohol, tobacco, MDMA, cannabis, and cocaine) is very common among those taking synthetic cathinones. 1,84 In addition, synthetic cathinones are often found in powders or pills resembling one another, potentially leading consumers to be unaware of the specific stimulant or combination of substances they are using. Adulteration by both substitution and addition is particularly relevant in this family of substances, as these mixtures increase the risk for consumers to encounter unforeseen adverse effects and potential harm.…”
Section: Cathinonesmentioning
confidence: 99%
See 2 more Smart Citations
“…84 However, not all the effects are only related to cathinone use, as polysubstance abuse (for example with alcohol, tobacco, MDMA, cannabis, and cocaine) is very common among those taking synthetic cathinones. 1,84 In addition, synthetic cathinones are often found in powders or pills resembling one another, potentially leading consumers to be unaware of the specific stimulant or combination of substances they are using. Adulteration by both substitution and addition is particularly relevant in this family of substances, as these mixtures increase the risk for consumers to encounter unforeseen adverse effects and potential harm.…”
Section: Cathinonesmentioning
confidence: 99%
“…89,90 Moreover, 4-MMC users reported a prolonged feeling of activity compared to cocaine. 1,81,84 Both animal and human studies have also suggested that methylone may possess an addiction potential like or greater than MDMA, although results suggested a lower potential for abuse and compulsive use than cocaine, methamphetamine, and 4-MMC. 42,79,91 On the other hand, an observational-naturalistic study conducted in humans to evaluate the acute pharmacological effects of methylone oral self-administration, showed that methylone was able to induce the prototypical psychostimulant and empathogenic effects generally associated with MDMA, although with lower intensity.…”
Section: Cathinonesmentioning
confidence: 99%
See 1 more Smart Citation